Effects of Transcranial Direct Current Stimulation on Information Processing Speed, Working Memory, Attention, and Social Cognition in Multiple Sclerosis - Grigorescu, Christina; Chalah, Moussa A.; Lefaucheur, Jean-Pascal; Kümpfel, Tania; Padberg, Frank; Ayache, Samar S.; Palm, Ulrich (Frontiers in Neurology, 2020)
Multiple Sclerosis (MS) is a chronic inflammatory disease of the central nervous system. Cognitive impairment occurs in 40-65% of patients and could drastically affect their quality of life. Deficits could involve general cognition (e.g., attention and working memory) as well as social cognition. Transcranial direct current stimulation (tDCS), is a novel brain stimulation technique that has been assessed in the context of several neuropsychiatric symptoms, including those described in the context of MS. However, very rare trials have assessed tDCS effects on general cognition in MS, and none has tackled social cognition. The aim of this work was to assess tDCS effects on general and social cognition in MS. Eleven right-handed patients with MS received two blocks (bifrontal tDCS and sham, 2 mA, 20 min, anode/cathode over left/right prefrontal cortex) of 5 daily stimulations separated by a three-week washout interval. Working memory and attention were respectively measured using N-Back Test (0-Back, 1-Back, and 2-Back) and Symbol Digit Modalities Test at the first and fifth day of each block and one week later. Social cognition was evaluated using Faux Pas Test and Eyes Test at baseline and one week after each block. Interestingly, accuracy of 1-Back test improved following sham but not active bifrontal tDCS. Therefore, active bifrontal tDCS could impair working memory via cathodal stimulation of the right prefrontal cortex. No significant tDCS effects were observed on social cognition. Admitting the small sample size and the learning (practice) effect that might arise from the repetitive administration of each task, the current results should be considered as preliminary and further investigations in larger patient samples are needed to gain a closer understanding of tDCS effects on cognition in MS.